Expression of secretory immunoglobulin A in gastrointestinal tract of streptococcal pneumonia rhesus monkey - CHEN Lian; LUO Qi-hui; ZHANG Yao; CHEN Zheng-li; CHENG An-chun; ZENG Wen (浙江大学学报. 农业与生命科学版)
Streptococcus pneumoniae is a conditional pathogenic bacteria which is associated with significant global morbidity and mortality. The main infection way is through mucosa system. Due to its variable serotype, there still have no effective method to prevent it. Secretory immunoglobulin A (SIgA) is the most important antibody secreted by plasmocytes and also the maximum in number, which can prevent bacterial adhesion to cells of host. Besides, secretory piece of SIgA can bind pneumococcal surface protein A, which help immune cells clear bacteria. Previous study showed that SIgA decreased when a host was infected with S. pneumoniae in the intestinal tract. SIgA could restrain bacteria being translocated to other organs and activate complement pathway, so when secretion decreased, host immune resistance become weakened, thus caused pathological changes. Corresponding to this research, increase of the antibody could help inhibit infection. This experiment aimed to investigate the expression condition of SIgA in intestinal mucosal immune system when rhesus monkeys were infected with S. pneumoniae spontaneously, and its role in the pathopoiesis of S. pneumoniae. Due to the high similarity of genes shared between human beings and rhesus monkeys, this experiment would also be helpful for the understanding of pneumonia happened on mankind.Three infected and three normal rhesus monkeys were blooded to death and obtained relative organs after anaesthesia. The changes of SIgA expression in esophago, jejunum, caecum, stomach and liver of rhesus monkeys were detected by immunohistochemistry and in situ hybridization on paraffin sections. Meanwhile, the images were collected, and the optical density value and positive cell area were detected by microscope.Immunohistochemistry results showed that the expression of SIgA in infected groups was smaller than that in normal ones, especially in jejunum where the expression was significantly reduced (P<0.05) (Table 1 and Fig. 1). Similar results were obtained by in situ hybridization test. The total areas of positive cells were reduced in infected groups, and the differences were significant (P<0.05) in jejunum, caecum, stomach (Table 2 and Fig. 2). Optical density values increased in infected groups, but the differences were not significant (P>0.05) compared with normal ones. Most of the positive cells concentrated in the mucous layer and some in the blood vessel, while in the liver they were diffused. The positive cells were principally lymphocytes, hepatocytes and cells in blood vessels, still some glandular cells, endotheliocytes, non-cuticular epitheliums.The results above suggest that since SIgA plays a dominant role in the mucosal immune system, it possibly involves in the S. pneumoniae infection and may participate in the clearance of S. pneumoniae through humoral immunity, and the reduction of the antibody may be one of the reasons for S. pneumoniae infection.